Effect of Hoof Trimming on Milk Yield in Dairy Cows with Foot Disease - Kibar, Murat; Çağlayan, Tamer (Acta Scientiae Veterinariae, 2016)
Backround: Milk is produced at the cost of other metabolic processes in the body and high milk yield has been associated with lameness and claw lesions. Lameness has also been associated with a decrease in milk yield. In the past, claw disorders and lameness in dairy cattle have been an increasing problem of the modern dairy industry. Hoof trimming is performed to prevent hoof lesions and improve gait by correction and maintenance of the hoof symmetry and shape. Lameness caused by hoof disorders can be treated by correct hoof trimming. The aim of this study was to test the hypothesis that one-time claw trimming affect the milk production in dairy cattle with hoof disorders on commercial dairy farms. Materials, Methods & Results: Milk yield level was examined before and after claw trimming in dairy cattle. Eighteen Holstein dairy cows were examined on a commercial dairy farm. Calving number, calving time, lactation number, lactation stage, culling date and milk yield in liters were detected from farm recording system. All cows were visual signs of claw disorders or lameness. Their hooves had not been were trimmed for several years. Trimming technique included leveling the 2 claws, aiming for symmetric bulbs. The axial and abaxial walls were both intended to be parts of the bearing surface and the 2 claws were trimmed flat and balanced with each other. The caudal two-thirds of the axial sole of both claws were sloped toward the interdigital area. All of the cows checked for hoof diseases. The period of observation spanned 45 d, starting day of claw trimming. The observation period was the lactation when the claw trimming was performed. Milk yield was performed one day before and 10, 30, and 45 days after hoof trimming. Cows that were in the mid to late lactation period were selected for the study. The mean days in milk for the group was 221.8 (150-272 days) and the mean number of calvings was 2.8 times (range: 2-5 times) before trimming. Discussion: The shape of the lactation curve is influenced by herd factors such as management and nutrition and individual factors like genetics, parity, and disease. Discrepancies in the literature with regard to the effect of lameness and claw lesions on milk yield are partly the result of these complex influences. Daily milk production of cows in the current study averaged 21 L/d, so milk weight represented approximately 3% of a cow’s body weight per milking. In this study cows were 2 to 5th lactation. Most hoof diseases are accrued around the time of calving. Hoof diseases is becomed visible on the bearing surface of the sole after 2 to 3 months such as white-line disease, sole ulcer, and hemorrhages. We assessed milk yield as the one time claw trimming performed, so any possible healing effect of claw trimming could have led to an underestimation of any negative effects of bad claw health on milk production. Cows with painful claw lesions eat less, are more reluctant to move, and might consequently produce less milk than cows without claw lesions. The significant associations between most claw disorders and increased yield in this study do not prove direct relationships. At claw trimming, the average lactation stage in first parity was 148 DIM; 25% of the cows were before 74 DIM and 25% were later than 226 DIM. After the claw trimming between days 10-30 and 10-45 were determined differences in milk yield (P < 0.05; P < 0.01). In conclusion, this study showed that one time hoof trimming during the lactation period changed the milk yield of the dairy cows with hoof diseases.